Peran Kecerdasaran Intelektual Dan Karakteristik Kewirausahaan Dalam Meningkatkan Kinerja Usaha Dengan Pengalaman Bertani Sebagai Variabel Moderasi - Nusron, Anis; Prasetyo, Rizqi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research aims to test the influence of intellectual intelligence and entrepreneurial characteristics on business performance, as well as test the influence of intellectual intelligence and entrepreneurial characteristics on business performance with farming experience as a moderation. The novelty of this research is the use of the farming experience variable as a moderating variable of the influence of intellectual intelligence and entrepreneurial characteristics on business performance. The population and sample used in this research were farmers (roses, jasmine and tuberose) in Rombo Kulon Village, Rembang District, Pasuruan Regency, totaling 73 people. The results of the research show that intellectual intelligence has a significant effect on business performance, while entrepreneurial characteristics have no effect on business performance, the moderation effect shows that farming experience is able to moderate the influence of intellectual intelligence on business performance and farming experience is not able to moderate the influence of entrepreneurial characteristics on business performance.